Cardiovascular outcomes and safety of SGLT2 inhibitors in chronic kidney disease patients - Chen, Xiutian; Wang, Jiali; Lin, Yongda; Yao, Kaijin; Xie, Yina; Zhou, Tianbiao (Frontiers in Endocrinology, 2023)
Background: Sodium-glucose co-transporters(SGLT)2 inhibitors have cardiovascular protection in patients with heart failure (HF) and type 2 diabetes mellitus (T2DM), but there is little evidence of their application in patients with chronic kidney disease (CKD) and there are inconsistent results. Therefore, in order to explore the cardiovascular protective effect of SGLT2 inhibitors in CKD population, we conducted a systematic review and meta-analysis to evaluate the cardiovascular effectiveness and safety of SGLT2 inhibitors in this population.Method: Search PubMed and Web of science database for Randomized controlled trial (RCT) of SGLT2 inhibitor in CKD patients, and build the database from Jan. 2023.According to the inclusion and exclusion criteria, the literature was screened, the quality of the literature was evaluated and the data was extracted. Revman5.3 and Stata17.0 were used for statistical analysis, and Hazard ratio(HR), Odd ratio(OR) and corresponding 95% Confidence intervals(CIs) were used for the analysis of outcome indicators.Results: Thirteen RCTs were included. In CKD patients, SGLT2 inhibitors reduced the risk of cardiovascular death (CVD) or hospitalization for heart failure (HHF) by 28%, CVD by 16% and HHF by 35%. And reduce the risk of all-cause death by 14%, without increasing the risk of serious adverse effect (SAE) and urinary tract infection (UTI), but increasing the risk of reproductive tract infection(RTI).SGLT2 inhibitor has cardiovascular protective effect on patients with chronic kidney disease, which can significantly reduce the risk of cardiovascular death, heart failure hospitalization and all-cause death, without increasing the risk of SAE and UTI, but increasing the risk of RTI.